Risk factors for detecting germline BRCA1 and BRCA2 founder mutations in Ashkenazi Jewish women with breast or ovarian cancer. Issue 5 (1st May 1999) - Hodgson, Shirley V; Heap, Elizabeth; Cameron, June; Ellis, David; Mathew, Christopher G; Eeles, Rosalind A; Solomon, Ellen; Lewis, Cathryn M
Abstract : We ascertained 184 Ashkenazi Jewish women with breast/ovarian cancer (171 breast and 13 ovarian cancers, two of the former also had ovarian cancer) in a self-referral study. They were tested for germline founder mutations in BRCA1 (185delAG, 5382insC, 188del11) and BRCA2 (6174delT). Personal/family histories were correlated with mutation status. Logistic regression was used to develop a model to predict those breast cancer cases likely to be germline BRCA1/BRCA2 mutation carriers in this population. The most important factors were age at diagnosis, personal/family history of ovarian cancer, or breast cancer diagnosed before 60 years in a first degree relative.  A total of 15.8% of breast cancer cases, one of 13 ovarian cancer cases (7.7%), and both cases with ovarian and breast cancer carried one of the founder mutations. Age at diagnosis in carriers (44.6 years) was significantly lower than in non-carriers (52.1 years) (p<0.001), and was slightly lower in BRCA1 than BRCA2 carriers. Thirty three percent of carriers had no family history of breast or ovarian cancer in first or second degree relatives. Conversely, 12% of non-mutation carriers had strong family histories, with both a first and a second degree relative diagnosed with breast or ovarian cancer.  The predicted values from the logistic model can be used to define criteria for identifying Ashkenazi Jewish women with breast cancer who are at high risk of carrying BRCA1 and BRCA2 mutations. The following criteria would identify those at approximately 10% risk: (1) breast cancer <50 years, (2) breast cancer <60 years with a first degree relative with breast cancer <60 years, or (3) breast cancer <70 years and a first or second degree relative with ovarian cancer.